2012
DOI: 10.3109/01443615.2011.639467
|View full text |Cite
|
Sign up to set email alerts
|

Late postpartum eclampsia

Abstract: Studies lack data regarding incidence, risk factors, optimal treatment and outcome of postpartum eclampsia (PPE), convulsions within 7 days (mostly convulsions occur within 24 - 48 h) after delivery of fetus placenta. However, convulsions can occur late, up to 4 weeks. After 48 h, it is late PPE. Late postpartum eclampsia without preceding pre-eclampsia is rare and poses a diagnostic challenge. An observational study was carried out to find the frequency of PPE, late PPE and clinical profile for prediction/pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 14 publications
1
23
1
2
Order By: Relevance
“…Animal data have shown that chronic nitric oxide blockade is associated with hypertension, proteinuria, and reductions in kidney function [72, 73]. Consistent with these observations, use of nitric oxide donors has shown benefit in a few human studies [7477]. In one case a successful pregnancy followed use of nitric oxide donors in a patient with scleroderma who had had preeclampsia in a preceding pregnancy [77].…”
Section: Therapies For Preeclampsia: Magnesium Sulfate Aspirin Cmentioning
confidence: 93%
See 1 more Smart Citation
“…Animal data have shown that chronic nitric oxide blockade is associated with hypertension, proteinuria, and reductions in kidney function [72, 73]. Consistent with these observations, use of nitric oxide donors has shown benefit in a few human studies [7477]. In one case a successful pregnancy followed use of nitric oxide donors in a patient with scleroderma who had had preeclampsia in a preceding pregnancy [77].…”
Section: Therapies For Preeclampsia: Magnesium Sulfate Aspirin Cmentioning
confidence: 93%
“…Consistent with these observations, use of nitric oxide donors has shown benefit in a few human studies [7477]. In one case a successful pregnancy followed use of nitric oxide donors in a patient with scleroderma who had had preeclampsia in a preceding pregnancy [77]. However, until this is validated in large scale, prospective randomized studies use of these nitric oxide donors cannot be recommended in all patients.…”
Section: Therapies For Preeclampsia: Magnesium Sulfate Aspirin Cmentioning
confidence: 98%
“…14 Although there has been the suggestion that postpartum eclampsia may occur in the absence of any prodrome or suggestive features, similar to eclampsia occurring in the antenatal period, many women do experience symptoms before the event and therefore screening by the measurement of BP and education regarding likely features continue to be important. 14 Our study demonstrated that most patients with eclampsia do not have their BP recorded shortly before the seizure. This is not surprising given that most women have only weekly antenatal appointments in the later third trimester and regular BP assessment is only performed in hospital.…”
Section: Discussionmentioning
confidence: 98%
“…There were two cases of late (>48 h after delivery) postpartum eclampsia in our study. [12][13][14] The USA has seen increasing rates of postpartum eclampsia, 15 with rates Benzodiazepine as initial therapy 4 (21%) No initial therapy given 6 (32%)…”
Section: Discussionmentioning
confidence: 99%
“…Pre-eclampsia/eclampsia usually occurs between 20 weeks of pregnancy to 48 h postpartum 9. The term late postpartum eclampsia (PPE) is used when eclamptic events occur between 48 h and 4 weeks after pregnancy 10. A large observational study suggested that late PPE involves about 14% of cases of eclampsia 10…”
Section: Discussionmentioning
confidence: 99%